Emerging opportunities to treat drug-resistant breast cancer: Discovery of novel small-molecule inhibitors against different targets - Chen, Ruixian; Zhou, Zhilan; Meng, Xiangyue; Lei, Yi; Wang, Yuxi; Wang, Yanyan (Frontiers in Pharmacology, 2025)
Breast cancer is now the most common malignancy among females. Numerous highly effective small-molecule inhibitors, such as tamoxifen and fulvestrant, have received clinical approval, significantly enhancing the therapeutic landscape of breast cancer. However, the emergence of drug resistance in some patients presents an unmet clinical need. Identifying resistance-related targets has been a key therapeutic strategy in combating drug-resistant tumors. Studies investigating the molecular characteristics and resistance mechanisms of breast cancer have unveiled novel targets, including cell cycle checkpoint molecules, breast cancer stem cell-related molecules, and anti-apoptotic proteins. Relevant small-molecule inhibitors have shown promising potential in overcoming drug-resistant breast cancer in both preclinical and clinical trials. In this review, we evaluate the resistance mechanisms of available targeted inhibitors for breast cancer and summarize innovative targeted strategies with the potential to overcome resistance, guided by clinical research.